Use the point slope equation: y - y1 = m(x - x1)
(-1, -3); m = 4
Plug these numbers in.
y - (-3) = 4(x - -1)
y + 3 = 4x + 4
y = 4x + 1
Answer:
B. Recursive
Step-by-step explanation:
I calculated it logically
Hello, please do not cheat on classwork on brainly, as this is against the honor code. Please do not continue this activity.
Step-by-step explanation:
given
3x + y = 9
Writing In slope intercept form , y = mx + c
y = -3x + 9
comparing the given equation with y = mx + c
slope (m) = - 3
y-intercept (c) = 9
Hope it will help :)
The anwser is ten because the number i saw is 14 estimate is ten.